A cohort study analysing outcomes following transanal haemorrhoidal dearterialisation (THD). Issue 2 (April 2021) - Patel, Rikesh; Rehman, Adeeb; Baig, Mirza; Kazem, M.Ali; Khan, Arif
Abstract: Background: Although conventional open haemorrhoidectomy and stapled haemorrhoidectomy are effective procedures, they can lead to significant post-operative pain with risks to continence. Current evidence favours transanal haemorrhoidal dearterialisation (THD) and targeted mucopexy to be an efficacious alternative to conventional modalities. Our aim was to assess the midterm outcomes following THD. Methods: Prospective data was collected for patients undergoing day case THD under a single consultant over a 9-year period (March 2009 to February 2018). Data collected included: intra-operative findings, post-operative pain (defined as requirement of analgesia in recovery), post-operative complications and requirement of further procedures. Results: Over this time period, 271 patients underwent THD, with 203 (74.9%) patients also undergoing targeted mucopexy for 2nd to 4th degree haemorrhoids. Only 4 (1.5%) patients suffered from post-operative complications, including significant bleeding (n = 1), urinary retention (n = 1) and constipation (n = 2). Post-operative pain was identified in only 10 (3.7%) patients; eight of which had simultaneously undergone an additional procedure (e.g. excision of anal polyps and skin tags). Only 5 (1.8%) patients were identified that required further haemorrhoidal invasive intervention subsequently. Conclusions: These results are comparable with national data and demonstrate that THD is a safe procedure for symptomatic haemorrhoids with minimal morbidity.